Związki zgody w polszczyźnie na Ukrainie (na materiale zebranym wśród młodzieży szkół polskich) .......... 231 - Korol, Lesia (Tożsamość na styku kultur: 4, 2021)
GRAMMATICAL AGREEMENT IN THE SPOKEN POLISH OF SCHOOL STUDENTS OF POLISH ORIGIN IN UKRAINEThe article shows the typical deviations from the Polish standard syntactic norm in the Polish language of students of Polish schools in Ukraine. They often concern agreements, particularly between the subject and predicate in plural past tense (for example, One poszli sobie do domu; Moi bracia uczestniczyły w tym konkursie). A common linguistic deviation from the norm is to classify the lexeme to grammatical gender other than in the Polish language, which is usually accompanied by a change in the inflectional paradigm (stara gimnazja, złota medal) and neutralization of functional oppositions of the masculine-personal and non-masculine genders, which consist in giving up consonant alternations in the nominative forms of masculine-personal nouns (moje kolegi, znajomy Polaki). Such deviations are most often the result of interference.